A abordagem clínica da bronquiolite aguda: revisão da literatura - Bruna Gomes Silva; Maria Eterna Eduardo dos Santos; Silvania Katiussa de Assis Gomes; Alexsandra Diniz de Veras; Vandésia Botêlho da Silva; Alessandra Costa Teixeira; Edneuza José Soares; Nivia Maria Cru Marques; Tarcísio de Almeida Silva; Eduardo Paulo Queiroz; Soelley Duarte Alves da Silva (Revista ft, 2026)
Acute bronchiolitis is a common respiratory infection in children under two years of age, often caused by the respiratory syncytial virus (RSV), and is one of the main causes of pediatric hospitalization. The objective of this investigation is to describe the main studies for the clinical approach to acute bronchiolitis in current pediatric literature. The methodology of the present study consists of a literature review with a time frame from 2019 to 2024, in the databases of PubMed, SciELO and EBSCO with the descriptors in English: bronchiolitis, virus, children, pediatrics and the use of the Boolean operators “AND” and “OR”. The analysis allows us to state that the diagnosis is purely clinical, based on symptoms such as wheezing, coughing and difficulty breathing, whereas tests are only used in severe cases. Treatment is supportive, with hydration and oxygen therapy, and there is no consensus on the use of medications such as bronchodilators and corticosteroids. Advances include the use of monoclonal antibodies such as Nirsevimab to prevent RSV, and technologies such as lung ultrasound for diagnosis. It is therefore concluded that bronchiolitis requires evidence-based clinical management, prioritizing non-invasive and humanized approaches. Theoretical reviews are important for pediatric practice and the need for multidisciplinary monitoring in the approach to bronchiolitis.